Some Sufficient Conditions for Persistency and Permanency of Two Stages DNA Splicing Languages via Yusof-Goode Approach - Mudaber, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad (2014)
Splicing system that was first introduced by Head makes a connection between field of formal language theory and molecular biology. This system modeled the biological process of splitting and ligating on double stranded deoxyribonucleic acid (DNA) molecules under effect of restriction enzymes and appropriate ligase. In this paper, the concept of two stages DNA splicing languages is introduced. Some sufficient conditions for persistency and permanency of the above DNA splicing languages focusing on two rules and two initial strings will be investigated by usingYusof-Good (Y-G) approach.